Effects of helium on mechanical properties of tungsten for fusion applications. (May 2018) - Miyazawa, Takeshi; Hwang, Taehyun; Tsuchida, Kohei; Hattori, Takaya; Fukuda, Makoto; Nogami, Shuhei; Hasegawa, Akira
Highlights: We conducted a high-energy He-implantation technique, post-implantation annealing and post-implantation tensile tests. We observed ductile fracture and no grain-boundary fracture on the ruptured surface of specimens after He-implantation. We found that 20 appm of He implantation is level enough to suppress the recrystallization of pure W. Abstract: The effects of helium (He) on mechanical properties of hot-rolled pure W were investigated using a high-energy He-implantation technique and post-implantation tensile tests. After the He implantation, the tensile specimens were heat treated at 1100 °C for 100 h in order to recrystallize the pure W. The post-implantation tensile tests were conducted in vacuum at 400 and 700 °C. The post-implantation annealed specimens showed almost the same hardness as-received unimplanted specimens. Tensile properties of He-implanted specimens after the post-implantation annealing indicated almost the same trend as those of as-received specimens under these experimental conditions. Dimples were formed and ductile fracture was observed on the ruptured surface of all specimens. No grain-boundary fracture surface was observed under these experimental conditions. The results showed that He clusters would suppress the recrystallization of hot-rolled pure W because the He clusters might form on dislocations in low angle grain boundaries or in cell walls in the matrix. Because of the suppression of recrystallization by the He clusters, the tensile properties of He-implanted specimens after post-implantation annealing show almost the same trend as those of as-received specimens under the experimental conditions. The results indicate that 20 appm of He implantation is level enough to suppress the recrystallization of pure W.